2010
DOI: 10.1016/j.addbeh.2009.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of generalized anxiety disorder and alcohol use disorders among individuals seeking outpatient substance abuse treatment

Abstract: The present study sought to address a gap in the literature by providing preliminary evidence of the prevalence and clinical characteristics of comorbid generalized anxiety disorder (GAD) and alcohol use disorders (AUD) in a front-line outpatient substance abuse clinic. Of 39 outpatients meeting criteria for an AUD, nearly half (46%) also met criteria for current GAD. The onset of GAD occurred prior to AUD in 67% of comorbid cases, with an average time lag of 12.5 years among individuals with primary GAD. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 15 publications
7
103
0
3
Order By: Relevance
“…In other words, patients who have anxious complaints or symptoms during or after SUD treatment might carry risks for using various substances to alleviate anxiety symptoms. As Smith and Book reported in their study, GAD interferes with SUD treatment [17]. In Oumete et al's follow-up study, comorbid AD impaired engagement in SUD treatment, and comorbid AD-SUD patients had worse results in functioning and symptom measures when compared with patients with SUD alone.…”
Section: Prognosis In Comorbiditymentioning
confidence: 82%
See 2 more Smart Citations
“…In other words, patients who have anxious complaints or symptoms during or after SUD treatment might carry risks for using various substances to alleviate anxiety symptoms. As Smith and Book reported in their study, GAD interferes with SUD treatment [17]. In Oumete et al's follow-up study, comorbid AD impaired engagement in SUD treatment, and comorbid AD-SUD patients had worse results in functioning and symptom measures when compared with patients with SUD alone.…”
Section: Prognosis In Comorbiditymentioning
confidence: 82%
“…In patients with opiate dependency, Rosen et al found the prevalence of PTSD and generalised anxiety disorder (GAD) as 27.8 and 29.7%, respectively [16]. Smith and Book analysed 56 patients with substance use disorder and postulated that 32% of the patient group met criteria for GAD [17]. Goldner et al made…”
Section: Diagnostic Tools Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The co-occurrence of generalized anxiety disorder (GAD) and alcohol use disorder (AUD) disorder with the rate of comorbidity ranging from 8.3% to 56.2% is well documented [45]. GAD was also found to be a relevant factor among individuals with alcohol use disorder seeking outpatient substance abuse treatment [46].…”
Section: Epidemiological Discussionmentioning
confidence: 99%
“…6 Rates of unemployment and social isolation are high, 4 as is concomitant alcohol and substance misuse in an attempt to alleviate symptoms. 7 People with GAD have high numbers of general practitioner (GP) visits and secondary care contacts, both because of associated physical/somatic symptoms and because GAD is often comorbid with chronic physical health problems. 8 The 2011 National Institute for Health and Care Excellence (NICE) guidelines entitled Generalised Anxiety Disorder and Panic Disorder (With or Without Agoraphobia) in Adults: Management in Primary, Secondary and Community Care 9 established good evidence for the effectiveness of low-intensity psychological interventions in GAD.…”
Section: Clinical Backgroundmentioning
confidence: 99%